Pervasiveness of microplastics in the gastrointestinal tract of some selected fish species from Turag River alongside the capital city of Bangladesh - HM Shahnewaz Khan; Jabed Hasan; Mohammed Manik; Murad Ahmed Farukh; Md Shahjahan (Emerging Contaminants, 2024)
Microplastics (MPs) are synthetic contaminants that have received global attention due to their ubiquitous occurrence, extreme durability, and capacity to harm ecosystems and human health. This study investigated the occurrence of MPs in three fish species (Channa striata, Puntius sophore and Anabas testudineus) collected from two locations (Ashulia Bridge and Mirpur Road) of the Turag River, which flows alongside the Dhaka city, Bangladesh. MPs abundance (items/individuals) was highest in Channa striata (3.8 ± 0.6) from the Ashulia Bridge area and lowest in Puntius sophore (1.8 ± 0.4) from the Mirpur Road area. Fiber was found to be the most dominant (89–93%) form of MPs followed by fragments (21–35%), films (0–26%) and foams (0–5%). The dominant color of MPs was blue (69–83%), then red (20–33%), black (11–14%), green (8–20%), and purple (6–8%). The majority (56–71%) of the MPs assessed were <0.5 mm in size, followed by 0.5–1.0 mm (29–33%) and 1–5 mm (38–53%). ATR-FTIR examination revealed three specific polymer varieties - PP (40%), PS (30%) and LDPE (30%). The results of this study provided a baseline of MPs pollution in one of the major protein sources freshwater fishes and raised concern on public health particularly who consume fishes from the urban waterways.